2017
DOI: 10.1149/2.0371708jes
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Structural and Transport Properties of Ionic Liquids with Cationic Oligoether Chains

Abstract: X-ray diffraction and molecular dynamics simulations were used to probe the structures of two families of ionic liquids containing oligoether tails on the cations. Imidazolium and pyrrolidinium bis(trifluoromethylsulfonyl)amide ILs with side chains ranging from 4 to 10 atoms in length, including both linear alkyl and oligo-ethylene oxide tails, were prepared. Their physical properties, such as viscosity, conductivity and thermal profile, were measured and compared for systematic trends. Consistent with earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 80 publications
5
50
0
Order By: Relevance
“…Comparing Pyr 1,4O1 TFSA and Pyr 1,1O4 TFSA, which have the same molecular weight and are structural isomers, the density was higher when the ether oxygen atom was located further from the pyrrolidinium ring. This may reflect the differences in the possible stable cation structures depending on the position of the ether oxygen atom in the side chain, [20,22,36] as will be discussed in detail later based on the results of MD calculations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing Pyr 1,4O1 TFSA and Pyr 1,1O4 TFSA, which have the same molecular weight and are structural isomers, the density was higher when the ether oxygen atom was located further from the pyrrolidinium ring. This may reflect the differences in the possible stable cation structures depending on the position of the ether oxygen atom in the side chain, [20,22,36] as will be discussed in detail later based on the results of MD calculations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the case of ammonium cations, it has been reported that the physicochemical properties of RTILs change depending on how the two ether oxygen species are introduced [17] . In pyrrolidinium‐based RTILs, many RTILs containing ether oxygen atoms have been reported, and their resulting physicochemical properties based on the introduction of ether oxygen atoms into the side chains have been investigated using both experimental and computational approaches [16,18–23] . However, few systematic studies have been carried out into the effects of the oxygen atom position on the physicochemical properties of these RTILs [20–22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rigidity of this adopted nanostructure is directly linked to the measured properties, leading to slower dynamics for more persistent structures. 28 Despite the dispute in the literature about the interrelations of different transport properties in ILs, their quantification and optimisation are still highly important for further development of and technical implementation of ILs. Quantification of the inter-relationship of transport properties and the development of a better understanding of the underlying transport mechanisms require systematic investigation of ILs.…”
mentioning
confidence: 99%
“…Although many factors can influence the dynamics of ILs, the higher proportion of anions to cations in the DIL (2 to 1) seems to overcome the fluidifying effect of ether chains, common in monovalent ILs. 48 The more concentrated charges increase Coulombic interactions that often strongly affect the viscosity. As a result, interactions between ether chains and imidazolium rings 49 could be forced, thus additionally increasing the viscosity.…”
Section: Physical Properties Of the Pure Ionic Liquidsmentioning
confidence: 99%